Enhancing the Efficiency of the Military Environmental Security System through the Implementation of Advanced Technical Means - Akhundov, Ramil; Hashimov, Elshan (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
The modernization of environmental security systems in the armed forces is a critical step toward ensuring operational safety under radiation and chemical threat conditions. This paper presents a framework for enhancing system efficiency through the integration of advanced technical means, including robotics, unmanned aerial vehicles (UAVs), distributed sensor networks, artificial intelligence (AI), and digital modeling technologies. The proposed methodology evaluates efficiency using a quantitative coefficient η = (A × R × C) / (Tr × E), which reflects improvements in accuracy, reliability, coverage, response time, and resource utilization. Results demonstrate that the introduction of these technologies increases overall system efficiency by 1.8–2.3 times compared to conventional approaches, reducing detection time by up to 50% and improving analytical accuracy by approximately 30%. The paper outlines an implementation roadmap that includes pilot testing, large-scale integration, and doctrinal adaptation. The findings confirm that innovation-driven modernization creates a more responsive, resilient, and data-driven environmental security system, capable of sustaining ecological and operational safety in both peacetime and combat environments.